2020
DOI: 10.18502/jpc.v8i2.3828
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin Prescription Pattern in a Teaching Hospital: The Promising Role of Antimicrobial Control Programs

Abstract: Background: Irrational use of antibiotics is a healthcare problem which can lead to antibiotic resistance. Vancomycin resistance is developing worldwide and is a huge financial burden to healthcare systems. Antimicrobial control programs are an essential component of educational programs in ensuring the optimal use of antibiotics. This study aimed to evaluate the effects of an educational program implemented at an Educational Medical Center on vancomycin prescription patterns. Methods: This was a cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Various studies have been performed to investigate the pattern of vancomycin use in different populations. For example a cross-sectional, pre-post interventional study conducted at Imam Hossein Hospital, Tehran, Iran, from 2014 to 2016 showed that total vancomycin consumption in the baseline and after the intervention phases was significantly reduced compared to the training program period [ 24 ]. In a study of 58 patients in Shiraz Namazi Hospital, it was shown that vancomycin was administered appropriately to 68.63% of patients with febrile neuropenia and 71.43% of patients with other diagnoses according to Healthcare Infection Control Practices Advisory Committee (HICPAC) and IDSA guidelines [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have been performed to investigate the pattern of vancomycin use in different populations. For example a cross-sectional, pre-post interventional study conducted at Imam Hossein Hospital, Tehran, Iran, from 2014 to 2016 showed that total vancomycin consumption in the baseline and after the intervention phases was significantly reduced compared to the training program period [ 24 ]. In a study of 58 patients in Shiraz Namazi Hospital, it was shown that vancomycin was administered appropriately to 68.63% of patients with febrile neuropenia and 71.43% of patients with other diagnoses according to Healthcare Infection Control Practices Advisory Committee (HICPAC) and IDSA guidelines [ 25 ].…”
Section: Discussionmentioning
confidence: 99%